Wedding Photography Marketing Communication Analysis: Analisis Komunikasi Pemasaran Fotografi Pernikahan - Muhammad Yhattaqun; Nur Maghfirah Aesthetika (Academia Open, 2022)
The era of globalization has given birth to increasingly fierce competition among companies, organizations or individuals who are currently doing business or are running a business, whether it's a business in the field of culinary, services, furniture and so on. Efficient and effective communication is needed to be able to convey ideas, thoughts, and feelings to all consumers, including the photography business. The photography business began to mushroom in the community who also needed to capture moments with family, partners or companies. The photo and video production house “Moonrise Photowork” is an example of a photography business that is developing in the community, especially in Sidoarjo Regency and Surabaya City. The purpose of this study was to determine the marketing communications carried out by "Moonrise Photowork". The method used is descriptive qualitative using the theory of IMC (Integrated Marketing Communication). Data collection techniques in this study were interviews and documentation. The result of this research is "Moonrise Photowork" conducts marketing communication using IMC very effectively to support customer loyalty. Highlights: The impact of globalization has intensified competition in various business sectors, including photography, necessitating efficient and effective communication strategies. Moonrise Photowork, a photo and video production house, serves as an example of a photography business thriving in Sidoarjo Regency and Surabaya City, catering to the growing demand for capturing meaningful moments. The study reveals that Moonrise Photowork effectively implements Integrated Marketing Communication (IMC) strategies, leading to enhanced customer loyalty and satisfaction. Keywords: globalization, photography business, marketing communication, Moonrise Photowork, customer loyalty.